Nursing care of a patient with diab etic kidney disease – a nursing process using the International Classification for Nursing Practice ICNP ® during the COVID-19 pandemic - Słomion, Magdalena; Stefanowicz-Bielska, Anna Marta (Nursing Problems / Problemy Pielęgniarstwa, 2022)
According to the World Health Organization, diabetes is a major cause of blindness, kidney failure, heart attacks, strokes, and lower limb amputations. The nursing process is a proposed plan of nursing care that encompasses a person’s biological, psychological, and social state. In 1989 the International Council for Nurses created the International Classification for Nursing Practice (ICNP®). The aim of this study is to present the process of nursing a patient with chronic diabetic kidney disease using ICNP® terminology during the COVID-19 pandemic. The study used the method of an individual case. The technique used included an interview, an observation, and an analysis of the patient’s medical records. Based on the case description, 12 sample diagnoses were created using standardized international terminology from the ICNP® dic-tionary. The most important health problems were presented. The patient was given appropriate nursing care. Health education was carried out.